Peningkatan Hasil Belajar dalam Materi Menghindari Perilaku Tercela dengan Metode Snowball Throwing Bagi Siswa Kelas VI SD No.107/IX Lopak Alai - Syamsidar Syamsidar (Jurnal Ilmiah Wahana Pendidikan, 2020)
This research is an effort to improve the learning outcomes of Islamic Religious Education through the Snowball Throwing method for grade VI SD No.107 / IX Lopak Alai students. This study aims to ask whether there is an increase in learning outcomes in the subject of Islamic Religious Education in the matter of Avoiding despicable behavior in grade VI SD No.107 / IX Lopak Alai academic year 2017/2018 using the Snowball Throwing Method. The application of the method used in this research is Classroom Action Research (PTK). The study was conducted in 2 cycles, each of which contained 4 stages, namely planning, implementing, observing and reflecting. The result of the average value in the pre-cycle was 64.07 with a completeness percentage of 25.92%. In the first cycle, the average value became 75.37 with a percentage of 66.66% completeness. In the second cycle it increased again with an average score of 86.48 students with a passing percentage of 92.59%. Thus it can be concluded that learning using the Snowball Throwing Method can improve the learning outcomes of Islamic Education in class VI SD No.107 / IX Lopak Alai in 2017/2018. Keyword: Learning Outcomes, Snowball Throwing Method